Can Instagram Attributes Affect Store Loyalty Mediated by Application Engagement and Interaction Intentions? - Palenewen, Endaina Yuki Hoonekita; Ariadi, Gede (JDM (Jurnal Dinamika Manajemen), 2023)
The amplifying importance of Instagram and its flourishing embracing proposes a massive prospect for firms to promote their products that deliver an endeavor to identify customers’ behaviors well. The research aims to recognize application attributes of perceived ease of use (PEOU), information quality, perceived usefulness, and system quality toward store loyalty from the Technology Acceptance Model (TAM) lens. Moreover, it elaborates on the theory of Planned Behavior (TPB) to construct interaction intention and application engagement as mediator variables that apply the conceptual model among application attributes and store loyalty. This study uses a quantitative approach where questionnaires are distributed to 272 consumers who know or follow the Instagram of the Coffee Shop in Salatiga, Indonesia. The outcomes expose which interaction intention and application engagement are essential in the linkages among perceived usefulness, system quality, and information quality toward the store. Conversely, both mediator variables could not mediate the linkages between PEOU and store loyalty. Theoretically, there is a synergy amid theory TAM and TPB, revealing that perceived usefulness is most influential as antecedents affect store loyalty through interaction intention and application engagement.